General theory of relativity - Kilmister, C. W. (Clive William) (Commonwealth and international library. Selected readings in physics., 1973)
General Theory of Relativity deals with the general theory of relativity and covers topics ranging from the principle of equivalence and the space-theory of matter to the hypotheses which lie at the bases of geometry, along with the effect of gravitation on the propagation of light. The motion of particles in general relativity theory is also discussed. This book is comprised of 14 chapters and begins with a review of the principle of equivalence, paying particular attention to the question of the existence of inertial frames in Newtonian mechanics. The beginnings and foundations of general re.